Real-world non-interventional post-authorization safety study of long-term use of burosumab in children and adolescents with X-linked hypophosphatemia: first interim analysis - Annemieke M. Boot; Gema Ariceta; Signe Sparre Beck-Nielsen; Maria Luisa Brandi; Karine Briot; Carmen de Lucas Collantes; Sandro Giannini; Dieter Haffner; Richard Keen; Elena Levtchenko; M. Zulf Mughal; Outi Mӓkitie; et al. (SAGE Publishing, 2024)
Background: X-linked hypophosphatemia (XLH) is a rare, progressive disorder characterized by excess fibroblast growth factor 23 (FGF23), causing renal phosphate-wasting and impaired active vitamin D synthesis. Burosumab is a recombinant human monoclonal antibody that inhibits FGF23, restoring patient serum phosphate levels. Safety data on long-term burosumab treatment are currently limited. Objectives: This post-authorization safety study (PASS) aims to monitor long-term safety outcomes in children and adolescents (1-17 years) treated with burosumab for XLH. This first interim analysis reports the initial PASS safety outcomes. Design: A 10-year retrospective and prospective cohort study. Methods: This PASS utilizes International XLH Registry (NCT03193476) data, which includes standard diagnostic and monitoring practice data at participating European centers. Results: At data cut-off (13 May 2021), 647 participants were included in the International XLH Registry; 367 were receiving burosumab, of which 67 provided consent to be included in the PASS. Mean (SD) follow-up time was 2.2 (1.0) years. Mean (SD) age was 7.3 (4.3) years (range 1.0-17.5 years). Mean duration of burosumab exposure was 29.7 (25.0) months. Overall, 25/67 participants (37.3%) experienced ⩾1 adverse event (AE) during follow-up; 83 AEs were reported. There were no deaths, no AEs leading to treatment withdrawal, nor serious AEs related to treatment. The most frequently reported AEs were classified as 'musculoskeletal and connective tissue disorders', with 'pain in extremity' most frequently reported, followed by 'infections and infestations', with 'tooth abscess' the most frequently reported. Conclusion: In this first interim analysis of the PASS, covering the initial 2 years of data collection, the safety profile of burosumab is consistent with previously reported safety data. The PASS will provide long-term safety data over its 10-year duration for healthcare providers and participants with XLH that contribute to improvements in the knowledge of burosumab safety. Trial registration: European Union electronic Register of Post-Authorisation Studies: EUPAS32190.